Community-Based Tourism in the Development of Curug Leuwi Hejo, Bogor - Rizki Nurul Nugraha; Apri Ramdani (Westscience Press, 2024)
Community participation is an important aspect in supporting the development of a tourist destination. Community participation can create sustainable tourism development, improve environmental sustainability, local economic growth, and community welfare. This research aims to understand the role of the community in efforts to develop tourist destinations in Curug Leuwi Hejo. This research uses qualitative methods, with descriptive qualitative analysis and SWOC analysis. Data collection was carried out by direct observation and interviews with managers and local communities. The results showed that community participation in the development of Curug Leuwi Hejo tourism is carried out through various forms of participation such as open meetings, environmental maintenance, training, responsibility, and local businesses. Community empowerment through awareness raising, job opening, and local craft development are also the main objectives in the concept of community-based tourism. Cultural preservation, such as through the maintenance of cultural heritage and the building of local cultural identity, is also an important aspect in the development of such tourist destinations. However, there are weaknesses and challenges that need to be addressed, such as limited community participation, limited nearby economic opportunities, lack of understanding of environmental impacts, lack of integration of local wisdom, and lack of government support for local initiatives. Appropriate strategies to take advantage of opportunities and overcome challenges, such as increasing community awareness, expanding ecotourism programs, strengthening the promotion of local wisdom and culture, strengthening partnerships with the government, and optimizing digital marketing.